PENERAPAN MATEMATIKA PADA ILMU EKONOMI: FUNGSI LINIER PAJAK DAN SUBSIDI - Savitri, Fhasa Dila; Khalid, Nayla; Kizul, Danya; Sari, Dhini Artika; Sholihah, Wardatus; Aji, Lindu (JIM : Journal Of International Management, 2024)
Linear functions of taxes and subsidies are fundamental concepts in economic analysis to measure the impact of fiscal policy on people's income and consumption. This article discusses the role of linear functions in determining the level of taxes and subsidies, and their effect on market equilibrium. Taxes serve to reduce consumers' purchasing power and increase government revenue, while subsidies aim to improve people's welfare by reducing consumption or production costs. Using a simple mathematical model, this study shows how changes in tax or subsidy rates affect disposable income, aggregate demand, and income distribution. The analysis indicates that progressive tax policies and well- targeted subsidies can improve resource allocation efficiency and economic justice. This research is expected to serve as a reference for policymakers in designing effective and sustainable fiscal instruments.